A tale of two lipids: Lipid unsaturation commands ferroptosis sensitivity. Issue 6 (13th January 2023) - Rodencal, Jason; Dixon, Scott J.
Abstract: Membrane lipids play important roles in the regulation of cell fate, including the execution of ferroptosis. Ferroptosis is a non‐apoptotic cell death mechanism defined by iron‐dependent membrane lipid peroxidation. Phospholipids containing polyunsaturated fatty acids (PUFAs) are highly vulnerable to peroxidation and are essential for ferroptosis execution. By contrast, the incorporation of less oxidizable monounsaturated fatty acids (MUFAs) in membrane phospholipids protects cells from ferroptosis. The enzymes and pathways that govern PUFA and MUFA metabolism therefore play a critical role in determining cellular sensitivity to ferroptosis. Here, we review three lipid metabolic processes—fatty acid biosynthesis, ether lipid biosynthesis, and phospholipid remodeling—that can govern ferroptosis sensitivity by regulating the balance of PUFAs and MUFAs in membrane phospholipids.